The Hudson's Bay Company's land tenures and the occupation of Assiniboia by Lord Selkirk's settlers [electronic resource] : with a list of grantees under the Earl and the company - Martin, Archer, 1865-1941 (London : W. Clowes, 1898)
Tables. Includes index. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44